Guidance for Studies Evaluating the Accuracy of Tuberculosis Triage Tests. (8th October 2019) - Nathavitharana, Ruvandhi R; Yoon, Christina; Macpherson, Peter; Dowdy, David W; Cattamanchi, Adithya; Somoskovi, Akos; Broger, Tobias; Ottenhoff, Tom H M; Arinaminpathy, Nimalan; Lonnroth, Knut; Reither, Klaus; Cobelens, Frank; et al.
Abstract: Approximately 3.6 million cases of active tuberculosis (TB) go potentially undiagnosed annually, partly due to limited access to confirmatory diagnostic tests, such as molecular assays or mycobacterial culture, in community and primary healthcare settings. This article provides guidance for TB triage test evaluations. A TB triage test is designed for use in people with TB symptoms and/or significant risk factors for TB. Triage tests are simple and low-cost tests aiming to improve ease of access and implementation (compared with confirmatory tests) and decrease the proportion of patients requiring more expensive confirmatory testing. Evaluation of triage tests should occur in settings of intended use, such as community and primary healthcare centers. Important considerations for triage test evaluation include study design, population, sample type, test throughput, use of thresholds, reference standard (ideally culture), and specimen flow. The impact of a triage test will depend heavily on issues beyond accuracy, primarily centered on implementation.